1931
DOI: 10.1111/j.1469-185x.1931.tb01026.x
|View full text |Cite
|
Sign up to set email alerts
|

The Respiration of Insects

Abstract: Summary The review covers the ground of external and internal respiration in insects, but deals neither with quantitative changes in metabolism, nor with the intimate processes of oxidation in the tissues. The general anatomy and histology of the tracheal system are described. The form of the tracheae and their mode of ending in the tissues is extremely varied in different insects and in different organs. The question whether the tracheal endings contain fluid or air and the problem of what forces keep the lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

1948
1948
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(27 citation statements)
references
References 76 publications
0
26
0
1
Order By: Relevance
“…reducing the length of the path over which oxygen needs to diffuse to reach internal tissues (33,34). It has been suggested that the evolution of gigantic insects in the Paleozoic was associated with a high level of atmospheric oxygen (13,17,18).…”
Section: Resultsmentioning
confidence: 99%
“…reducing the length of the path over which oxygen needs to diffuse to reach internal tissues (33,34). It has been suggested that the evolution of gigantic insects in the Paleozoic was associated with a high level of atmospheric oxygen (13,17,18).…”
Section: Resultsmentioning
confidence: 99%
“…In fact as far back as 1931, Wigglesworth noted that it was generally accepted that respiratory movements such as abdominal and thoracic pumping function to alternately compress and dilate the tracheal system (Wigglesworth, 1931). However, the mechanical problem with this idea is that taenidal rings, which are thickenings in the tracheal wall, can be viewed as morphological specializations that prevent rather than promote collapse.…”
Section: Observations Of Collapsible Tracheae In Insectsmentioning
confidence: 99%
“…Second, aside from a few basal groups, most insects are understood to have continuous, non-compartmentalized tracheal systems (e.g. Hetz, 2007;Wigglesworth, 1931), and our highresolution x-ray images have not revealed any evidence of valving or compartmentation in the tracheal system of Pterostichus stygicus. Direct confirmation that tracheal compression drives air through the spiracles will require measurement of airflow through the spiracles, or the contributions of convection and diffusion could be quantified by manipulating the density of the air in the flow-through system by replacing N 2 with SF 6 or helium.…”
Section: The Role Of Convection In Pterostichus Stygicusmentioning
confidence: 99%
“…Insects rely primarily on their tracheal system to exchange respiratory gases with the atmosphere (Wigglesworth, 1931). The system consists of air-filled tubes that open to the air through spiracles on the surface of the thorax and abdomen, branch throughout the body, and eventually reach the cells with blindended tracheoles.…”
Section: Introductionmentioning
confidence: 99%